STUDY OF ASBAB AN NUZUL:THE URGENCY OF KNOWING ASBAB AN NUZUL IN THE INTERPRETATION OF THE QUR'AN - Erik Lis Setiawan; Bidayatul Hubbil Iffah (BAMALA Institute, 2025)
This research discuss about Asbab an nuzul or the reasons for the revelation of verses from the Qur'an as one discipline important in the science of interpretation. The purpose main study This is to understand definition , history , types , and urgency learn Asbab an nuzul in an attempt reveal the meaning contained in the Qur'an comprehensively . Method used nature qualitatively using​ approach descriptive analytical through study literature classic and contemporary . The results of this study show that knowledge about Asbab an nuzul own very important role in understanding context historical revelation of verses , avoiding error interpretation , as well as clarify the laws and wisdom contained in revelation . Apart from that , understanding Asbab an Nuzul help connect meaning text with reality social and cultural at the time the Qur'an was revealed, so produce greater understanding​ complete and relevant to life contemporary Muslims .​ Thus , study​ about Asbab an nuzul not only important for interpreters , but also for all over Muslims who want to delve into message divine in more in-depth and contextually.